Analysis of Factors Affecting Liquidity of Islamic Banking Listed on the Indonesia Stock Exchange - Wiwin Yustina; Tulus Suryanto; Heni Noviarita; Erike Anggraeni (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
The purpose of this study is to investigate the effect of Non-Performing Financing, Third Party Funds, Financial To Funding Ratio, Macroprudential Intermediation Ratio and Macroprudential Liquidity Buffer on the liquidity of Islamic Banking listed on the Indonesia Stock Exchange List in the 3rd and 4th quarters of 2018 to the 1st and 2nd quarters of 2018. 2019. The research design used is a quantitative approach. The data analyzed is secondary data in the form of quarterly banking financial statements listed on the Indonesia Stock Exchange List for the 3rd and 4th quarters of 2018 to 1st and 2nd quarters of 2019, data for each bank. The population in this study were 15 Islamic banks listed on the Indonesia Stock Exchange List during the study period, with a sample of 12 Islamic banks during 4 quarters of observation, so that the final sample was 48 observational data. The results of the study show that the variables of Non Performing Financing, Financial To Funding Ratio have an influence on the liquidity of Islamic banking. While other variables, namely Third Party Funds, Macroprudential Intermediation Ratio and Macroprudential Liquidity Buffer, have no effect on the liquidity of Islamic Banking. Liquidity management in banking institutions is one aspect that becomes a top priority. Liquidity is a condition where banks are able to meet their obligations as they fall due and banks are able to meet the demand for funds by customers. Banks must be able to maintain their liquidity level in a safe and optimal position in accordance with the bank soundness level parameters set by Bank Indonesia.